PEMBELAJARAN DENGAN MENGGUNAKAN MULTIMEDIA DIGITAL - Abhanda Amra (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2012)
Digitalization gives great influences on education and social lives. In education, instructional media have shifted from conventional ones to digital ones. Even, the development has greatly taken place compared to the last decades. Formerly, teachers were the only media providers and if one want to get information, they should visit information center. Nowadays, some unlimited resources are available, even in one’s personal computer. In relation to using multimedia for learning must be under consideration that media is the best source of needed educational information.Kata kunci: media, pembelajaran, multimedia, digital